ChemInform Abstract: Electrophile‐Induced C—C Bond Activation of Vinylcyclopropanes for the Synthesis of Z‐Alkylidenetetrahydrofurans. Issue 21 (2nd May 2013) - Ganesh, Venkataraman; Kundu, Taraknath; Chandrasekaran, Srinivasan
Abstract The reaction is stereospecific and proceeds via bromenium‐catalyzed C—C bond activation of vinyl cyclopropanes and the following cyclization to alkylidenetetrahydrofuran and other heterocycles.